2021
DOI: 10.24843/jitpa.2021.v06.i02.p01
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antimikroba Kefir Susu Sapi yang Diinkubasi pada Tempurung Kelapa Hijau Muda terhadap Staphylococcus aureus dan Escherichia coli

Abstract: Penelitian ini bertujuan untuk mengetahui aktivitas antimikroba kefir susu sapi yang diinkubasi pada tempurung kelapa hijau muda terhadap Staphylococcus aureus dan Escherichia coli. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan tiga perlakuan dan lima ulangan. Ketiga perlakuan yaitu: kefir susu sapi yang diinkubasi didalam wadah toples atau kontrol (P0), kefir susu sapi yang diinkubasi pada tempurung kelapa hijau muda tanpa daging (P1), kefir susu sapi yang diinkubasi pada tempurung kelapa hij… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The number of lactic acid bacteria will greatly influence the volatile compounds that cause the sour aroma in kefir. This is supported by Yuniarti et al (2021) [15] reported that the total lactic acid bacteria of kefir fermented with green coconut shell meat was 14.3 x 106 CFU/g. So that the aroma produced in all treatments (P 1 , P 2 , P 3 and P 4 ) is the same acid.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…The number of lactic acid bacteria will greatly influence the volatile compounds that cause the sour aroma in kefir. This is supported by Yuniarti et al (2021) [15] reported that the total lactic acid bacteria of kefir fermented with green coconut shell meat was 14.3 x 106 CFU/g. So that the aroma produced in all treatments (P 1 , P 2 , P 3 and P 4 ) is the same acid.…”
Section: Discussionsupporting
confidence: 57%
“…However, the use of coconut shells in the fermentation process has added value, because there are bioactive compounds in coconut which causes this food to be classified as a functional food. This was reported by Yuniarti et al (2021) [15] that the antimicrobial activity of cow's milk kefir fermented with meat in green coconut shells is higher than the control, as evidenced by the formation of a clear zone diameter in inhibiting bacterial growth Staphylococcus and Escherichia coli. Based on the panelist response data (Table 2.)…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations